Ответ:
а) корней нет
б) х = 0, (48)
в) х = -1,5
Объяснение:
а) 3х - ( 4х + 5) = 3 - (2х - 3х)
-х - 5 = 3 - 2х + 3х
-8 = 0х
х ∈ ∅
Ответ: корней нет.
б) 3,5х - 6,1х - 5х = 3,2 - х
6,6х = 3,2
х = 3,2: 6,6
х = 0, (48)
Ответ: 0, (48)
в) 5х - 2 = 4 · (5х - 3х)
5х -2 = 20х - 12х
5х - 20х + 12х = 2
-3х = 2
х = -1,5
Ответь: -1,5
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
а) корней нет
б) х = 0, (48)
в) х = -1,5
Объяснение:
а) 3х - ( 4х + 5) = 3 - (2х - 3х)
-х - 5 = 3 - 2х + 3х
-8 = 0х
х ∈ ∅
Ответ: корней нет.
б) 3,5х - 6,1х - 5х = 3,2 - х
6,6х = 3,2
х = 3,2: 6,6
х = 0, (48)
Ответ: 0, (48)
в) 5х - 2 = 4 · (5х - 3х)
5х -2 = 20х - 12х
5х - 20х + 12х = 2
-3х = 2
х = -1,5
Ответь: -1,5